Application of the Rasch Model to the Evaluation of Biological Problems - Ida Elfira; Abdul Razak; Syamsurizal; Helendra (Journal of Education Reseach and Evaluation, 2024)
Evaluation of student abilities in Biology subjects often faces challenges in ensuring that the instruments used actually measure what they are supposed to measure. The data analysis used is the Rasch model, which is part of item response theory, offering a more accurate approach in analyzing evaluation data. This model allows the identification of items that are inappropriate or too difficult, as well as providing more in-depth information about individual student abilities.  Through analysis of instruments and question items from 30 multiple choice questions that emphasize critical thinking skills, the aim of this research is to assess the quality of Biology questions for class X SMA. Testing was carried out using WinStep software and Rasch modeling analysis on 166 students from five high schools/vocational schools. The research method used is quantitative. The results of the instrument investigation show that the issue has very good dependability and the unidimensionality of the instrument is indicated by unexplained changes in the first differentiation. These results show that the Rasch test can help educators in selecting questions that meet the evaluation criteria and contribute to improving the quality of national education. The implications of this research are By applying the Rasch Model, educators can develop more accurate and fair evaluation tools, which are able to identify individual student difficulties and strengths.